OKRA MUCILAGE - METHOD OF EXTRACTION AND A NOVEL STRATEGY FOR PHARMACEUTICAL DRUG DELIVERY SYSTEM (Journal of Pharmaceutical Negative Results, 2023)
This paper summarizes the current approaches in method of extraction of okra mucilage and application in pharmaceutical drug delivery system. Okra is a species of Abelmoschus esculentus L. belongs to the family of malvacae. In India, medicinal activity of okra is reported in traditional system like Unani, siddha and Ayurveda. Pharmacological uses of okra are anti-cancer, anti-diabetic, anti-oxidant, anti-microbial and anti-ulcer activity. Easily available in tropical and sub-tropical countries, non-toxic, biodegradable and cost effective used as excipient. Okra mucilage’s were extracted in different method using acetone, ethanol etc. It is a property of highly viscous the may retard the drug in sustained release. This article mainly scrutinized that okra mucilage approaches in pharmaceutical drug delivery system.